Feasibility study of a Behavioural Intervention for Opioid Reduction (BIOR) for patients with chronic non-cancer pain in primary care: a protocol. Issue 1 (18th January 2023) - Poole, Helen M; Frank, Bernhard; Begley, Emma; Woods, Aimee; Ramos-Silva, Andreia; Merriman, Mike; McCulough, Roisin; Montgomery, Catharine
Abstract : Introduction: Around 30%–50% of adults suffer moderate to severe chronic pain not caused by cancer. Significant numbers are treated with opioids which over time may cease to be effective and produce side effects (eg, nausea, drowsiness and constipation). Stopping taking opioids abruptly can cause unpleasant withdrawal effects. Tapering in small steps is recommended, though some patients might struggle and need support, particularly if they have limited access to pain management alternatives. Awareness of the potential risks as well as benefits of tapering should be explored with patients. Methods and analysis: A randomised controlled pilot feasibility study to investigate the effectiveness and feasibility of reducing high doses of opioids through a tapering protocol, education and support in primary care. Working with NHS Knowsley Place, we will identify patients taking 50 mg or above morphine equivalent dose of opioids per day to be randomly allocated to either the tapering group or tapering with support group. At an initial joint appointment with a pain consultant and General Practitioner (GP) GP tapering will be discussed and negotiated. Both groups will have their opioid reduced by 10% per week. The taper with support group will have access to additional support, including motivational counselling, realistic goal setting and a toolkit of resources to promote self-management. Some patients will successfully reduce their dose each week. For others, this may be more difficult, and the tapering reduction will be adjusted to 10% per fortnight. We assess opioid use, pain and quality of life in both groups at the start and end of the study to determine which intervention works best to support people with chronic pain who wish to stop taking opioids. Ethics and dissemination: The Behavioural Intervention for Opioid Reduction feasibility study has been granted full approval by Liverpool Central Research Ethics Committee on 7 April 2022 (22/NW/0047). The current protocol version is V.1.1, date 6 July 2022. Results will be published in peer-reviewed journals and disseminated to patient stakeholders in a lay summary report available on the project website and in participating GP surgeries. Trial registration number: ISRCTN 30201337.